Agen Branchless Banking Untuk Mencapai Masyarakat Bankable - Yuliaty, Tetty; Lubis, Arlina Nurbaity (BISNIS, 2017)
The potential of Branchless banking is good enough for revolution of payment system in the emerging markets. Which aims to expand financial services to unbanked communities and provide a platform to contact MSMEs to the global economy can be achieved. Bank Indonesia (BI) targets the percentage of people reaching bankable services to reach 50% by 2019. By the end of 2014, the new bankable group reaches 36%. Meanwhile, as many as 64% are unreached groups of services from banks (unbankable), now our society tend to have mind-minded economy mindset. For that, need an increase from the side of savings. Digital financial services (LKD) such as Branchless Banking initiated by Bank Indonesia may be part of this intermediation. Some of the reasons that make the unbankable group exist, ie they do not understand how to open an account. In addition, people may also prefer to save themselves, shy with the formalities, or they are no money. Branchless Banking Agent as one of the elements in the implementation of Branchless Banking very need to be studied existence. To assist this research, and also use primary data needed and secondary in the implementation, in-depth interviews, observation and other in reviewing this qualitative research. The purpose of this study was to determine whether branchless banking agents were able to reach the bankable community. Methods of data collection in this study are, documentation studies, Direct observation, Indepth interview Open Questions, as well as provide a question sheet to the respondents and other sources. Qualitative Data Analysis Method used in this research is successive approximation method. The results of this study indicate that Agent Banking is able to become one of the elements in achieving Bankable society, where with its existence, its proximity and intensity with unbanked communities, can slowly increase bankable society.